How to develop self-confidence & influence people by public speaking - Carnegie, Dale, 1888-1955 (Gallery Books, 2017)
Drawing on Dale Carnegie's years of experience as a business trainer this book will show you how to overcome the natural fear of public speaking, to become a successful speaker and even learn to enjoy it.